TINGKAT DEPRESI, ANSIETAS DAN STRES PASIEN GAGAL GINJAL KRONIK (GGK) DENGAN HEMODIALISA - Mimi Amaludin; Defa Arisandi; Nurpratiwi Nurpratiwi; Ali Akbar; Fauzan Alfikrie; Uti Rusdian Hidayat; Debby Hatmayakin (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2023)
Chronic Kidney Disease (CKD) is becoming a serious health problem with an increasing number of cases. CKD also has the second highest burden of medical costs after heart disease. The causes of kidney failure are currently dominated by hypertension and diabetes mellitus. As an action that must be done in CRF patients is to undergo hemodialysis. Hemodialysis is a transition of kidney function and role assisted by a dialyzer machine. Besides helping the role and function of the kidneys, hemodialysis has an impact on psychology with the emergence of anxiety, stress to depression. The aims to see the level of depression, anxiety & stress of CKD patients undergoing hemodialysis. This study was conducted using descriptive design and sampling techniques using purposive sampling. The level of depression, anxiety and stress was measured by the Depression, Anxiety, Stress Scale questionnaire (DASS 42) consisting of 42 statements with a sample of 75 people. The results found that 5 patients (6.7%) experienced mild anxiety, 43 patients (57.3%) were moderately anxious, 17 patients (22.7%) experienced severe anxiety and 7 patients (9.3%) experienced very severe anxiety. The stress level of 12 patients (16.0%) experienced mild stress, 14 patients (18.7%) moderate and 2 patients (2.7%) experienced severe stress and the level of depression 20 patients (26.7%) with mild depression, 39 patients (52.0%) moderate depression and 7 patients (9.3%) experienced severe stress. From this study, it can be concluded that there is anxiety, stress and depression in CKD patients undergoing hemodialysis.